A creature was stirring [videorecording (DVD)] - Wells, Shannon; Metz, Chrissy, 1980-; Basso, Annalise, 1998-; Paolo, Connor, 1990-; Compton, Scout, 1989- (Well Go USA Entertainment, 2024)
Faith keeps her troubled teenage daughter on a tightly controlled regimen of experimental drugs, their only means of fending off a mysterious, terrifying affliction. But after two burglars attempt to rob the home on Christmas, they stumble upon a long-kept family secret with monstrous consequences.